2016
DOI: 10.1016/j.jamcollsurg.2016.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Circulating Tumor Cells Identified Before Surgical Resection in Nonmetastatic Breast Cancer Patients

Abstract: Background Circulating tumor cells (CTCs) can be identified in approximately 25% of non-metastatic breast cancer patients (BC), and data are emerging regarding their prognostic significance. We hypothesized that CTCs identified prior to resection of the primary tumor would predict worse outcome in non-metastatic BC patients. Study Design We performed CTC enumerations on 509 patients with non-metastatic BC as part of an IRB approved study. CTCs (per 7.5 ml blood) were identified using the Cell Search® System … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…In the present study, we firstly demonstrated total CTCs, mesenchymal CTCs and CTC-WBC before or after surgery showed little association with clinical characteristics in T 1-3 N0M0 renal cancer patients. In non-metastasis breast cancer, the preoperative CTCs were also poorly associated with tumor size, grade or lymph node status [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we firstly demonstrated total CTCs, mesenchymal CTCs and CTC-WBC before or after surgery showed little association with clinical characteristics in T 1-3 N0M0 renal cancer patients. In non-metastasis breast cancer, the preoperative CTCs were also poorly associated with tumor size, grade or lymph node status [26].…”
Section: Discussionmentioning
confidence: 99%
“…CTCs and circulating tumor DNA are cells or DNA that have been shed by the tumor into the systemic circulation; these can be indicators of residual disease following treatment and are likely to represent an important mechanism through which a tumor can metastasise (123,124). CTCs have been detected in up to 30% of non-metastatic BC patients and their presence (even just one CTC) has been shown to be prognostic for recurrence-free survival and overall survival (125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135). CTC detection is also related to metastasis and poor survival in lowrisk patients with lymph node negative disease who did not receive adjuvant therapy (133).…”
Section: Blood-associated Biomarkers Of Tumor Radiosensitivitymentioning
confidence: 99%
“…In this battle between immune system and tumor, many apoptotic and necrotic tumor cells are phagocytized, increasing the concentration of cell-free DNA (cfDNA) in the blood which can be used as liquid biopsy. In some cases, this process starts very early, even in the absence of the primary site formed (10)(11)(12)(13). In this context, in the course of carcinogenesis and invasion of tumor cells in the bloodstream, white blood cells (WBC) are constantly undergoing molecular alterations.…”
Section: Methylation Profiling In Promoter Sequences Of Atmmentioning
confidence: 99%